Direct solutions of nth-order IVPs by homotopyperturbation method - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak (Taylor & Francis, 2010)
In this paper, a class of linear and nonlinear nth-order initial value problems (IVPs) is considered. The solutions of these IVPs are obtained by the homotopy-perturbation method (HPM). The HPM can be considered as one of the new methods belonging to the general classification of perturbation methods. Generally, the HPM deals with exact solvers for linear differential equations and approximative solvers for nonlinear equations. Several test cases are chosen to demonstrate the efficiency of HPM.